Growth development and fecundity of the earthworm Aporrectodea caliginosa after exposure to two organophosphates - Booth, L.H.; Heppelthwaite, V.J.; O'Halloran, K. (New Zealand Plant Protection, 2000)
The effect on fecundity of two organophosphates chlorpyrifos and diazinon was assessed in the earthworm Aporrectodea caliginosa Juveniles were exposed to two sublethal concentrations of each organophosphate the lowest of which was a laboratorysimulated field rate for 4 weeks and recovery was monitored for 12 weeks in organophosphatefree soil Growth maturation cocoon production and hatching success in resulting adults was monitored Growth was reduced by both pesticides during exposure but not in the recovery phase Chlorpyrifos affected maturation rates and fecundity at the highest concentration but diazinon had no effect at either concentration These preliminary results suggest no effects of these pesticides at field rates but the effects of longer term pesticide exposure on fecundity should be determined